Towards a funded system of social security: Design and implications - The case of Germany - - Hans H. Glismann; Ernst-Jürgen Horn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
What would a feasible system of social security in Germany have looked like in the year of 1995 and beyond? In order to find an answer we describe three base systems: ( l ) a purely funded system of social security, (2) a fully mandatory funded system of social security, and (3) a partially mandatory funded system. It is argued that - neglecting problems of transition - a purely funded system would be the best in economic terms; a fully mandatory funded system would need almost as many controls as the currently prevailing system (often labelled pay-asyou- go system). A partially mandatory funded system, assuring some kind of basic income, would need less controls and less governmental authority than the fully mandatory system but more than a funded system. After quantification of two scenarios which represent components of the three base systems, a system of taxation with respect to contributions and/or benefits is discussed which is at the same time simple in terms of costs of bureaucracy and does not tax economic growth more than necessary.
Keywords: 330